SAUDI ARABIA'S VISION 2030: IMPLICATIONS FOR WOMEN - TECKCHANDANI, JYOTIKA; DHINGRA, RITIKA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Aiming to diversify the Kingdom's oil-dependent economy and promote a more inclusive society, Saudi Arabia's Vision 2030 is a bold and revolutionary agenda. One of its most noteworthy aspects is the deliberate focus on women's empowerment, a field that has historically been limited by conservative views of gender roles. This vision places women as key players in the future of the country and is not just an economic blueprint; it is a socio-political reconfiguration. A number of legislative changes have been implemented as part of Vision 2030 to increase women's involvement in public life. These include expanding women's access to the workforce, encouraging female entrepreneurship, easing guardianship laws for men, and lifting the driving ban in 2018. As a result, women now hold leadership roles in ministries, financial institutions, and even the diplomatic corps, and the female labor force participation rate has more than doubled in recent years. Women now have more options thanks to educational reforms, especially in “STEM (science, technology, engineering, and mathematics)” fields. However, the path to complete gender parity is still complicated, despite the fact that these advancements represent unquestionable progress. Meaningful inclusion is still hampered by societal norms, legal ambiguities, and structural barriers. The state-led reform narrative also raises critical questions: Are these changes reflective of a genuine shift in gender ideologies, or are they driven primarily by economic imperatives and global image-making? This paper critically evaluates how Saudi Arabia's Vision 2030 has affected women's status by examining both official policies and popular reactions. It looks into whether Vision 2030 is a top-down approach to modernization strategy with little potential for transformation or a route to long-term gender equity, drawing on government data, international reports, and feminist critiques. At the same time the Saudi example provides insightful information about how patriarchal systems and state-driven ideas of change interact in the Arab Gulf.